POTENSI CACING TANAH EKSOTIK ENDOGEIK Pontoscolex corethrurus UNTUK PRODUKSI VERMIKOMPOS GRANUL (VERMIGRAN) BERBASIS BAHAN ORGANIK LOKAL - Dewi, Widyatmani Sih; Sumarno, Sumarno; Rossati, Sri (Caraka Tani - Jurnal Ilmu Ilmu Pertanian, 2012)
The potential of  Exotic  Earth worm  Endogeik  (Pontoscolex corethrurus)  for Production Vermikompos    granules (Vermigran) Local Organil-Based Materials. In 2011, total demand for  organic fertilizer in Indonesia was 12.394 million tons and 2.601 million tons  of new available. This requirement will continue to increase until 2015, so the  opportunity   to   develop   great organic fertilizer. One  disadvantage  of the  use of organic fertilizers is very much in    volume (bulky), it is necessary    vermikompos manufacturing  innovation in   the   form   of granules to   be   more efficient   in   the applicationand transport. Research objectives are: (1) study the potential     of earthworms in producing vermikompos Pontoscolex    corethrurus of l local organic ingredients, and (2)produce quality vermikompos in the form of  granules.  The study    was   conducted in   a   greenhouse Fak. Agriculture and in   the   yard   of a house in Ngesrep,   Boyolali, in July-November 2011. The     study design using a Completely  Randomized Design, factorial,two factor. Factor 1 is  composed of three types  of  worms   cedar, and  the  second  factoris  the variation  of the  type of organic material, consisting of 7 cedar. The variablesmeasured were vermikompos nutrient quality and speed  of the  water  solubility  vermikompos   granules. The  results showed  that  Pontoscolex corethrurus high potentialto produce vermikompos  that meet ISO   quality   compost.   Cow   pile, pile quail, water  hyacinth   can  be  used as  a  raw material   vermikompos.   Clay,   starch, starch and claymixture (1:1) can be  used as  an adhesive vermikompos granules (vermigran) soluble in   water at <48 hours. Production vermigran great potential for   developmentas a high-quality organic fertilizer.